PENGARUH PERAN PENGAWAS MENELAN OBAT (PMO) TERHADAP KEPATUHAN PENDERITA TUBERKULOSIS DALAM MENGIKUTI PROGRAM PENGOBATAN DOTS (DIRECTLY OBSERVED TREATMENT SHORTCOUSE) - Nilna Sa’adatar Rohmah; RR. Sri Ratna Rahayu; Fitri Indrawati (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Tuberculosis (TBC) treatment regimens require the introduction of PMO (Drugs Swallowing Drug) standardized on International Standards for Tuberculosis Care (ISTC) with DOTS strategy (Directly Observed Treatment Shortcouse). The goal of controlling new challenges such as TB/HIV co-infection, Multi Drug Resistance (MDR), Extensively Drug Resistance (XDR) and Loss to follow-up. Objective: Type of cross sectional study. Population 35 PMO using saturated samples. Methods: The instruments used are questionnaires and in-depth interviews. Data analysis is univariate, bivariate and multivariate. Results: The result of the study was the relationship between the role of PMO from family members in the supervision of taking medicine (p=0,024), there was a relationship between the role of PMO from family members in drug taking assistance in Fasyankes (p=0,002) and there was relationship between the influence of PMO role from family member accompaniment of sputum checks in Fasyankes (p=0,005) to TBC patient compliance. Conclusion: There is a statistical correlation between the roles of PMO from the family towards adherence to tuberculosis patients. Suggestion of research is given to related parties be reformed TBC control policy related to election criteria of PMO coming from family member in Semarang regency.